PENGABDIAN DALAM MENGOPTIMALISASIKAN KEGIATAN PEREKONOMIAN UMKM DI KELURAHAN BATU SEMBILAN MELALUI PROGRAM DIGITALISASI UMKM KERUPUK TEMPE - Salihi, Salihi (P3M STIE Pembangunan Tanjungpinang, 2024)
This service aims to develop digital literacy-based MSMEs for business actors in the Batu Sembilan Village, Tanjungpinang City. One of the SMEs in the Batu Sembilan sub-district, East Tanjungpinang sub-district, is the Tempe Crackers MSME. The methods in this service are surveys, observations, training documentation and direct assistance in the field with the aim of MSME owners having new knowledge about digitizing MSMEs that every MSMEs should have done and used this digital literacy, which can be obtained at low cost and free of charge